KONSEP PENDIDIKAN ISLAM IKHWAN AS-SHAFA (Suatu Kajian analisis Kritis) - La Rajab (IAIN Ambon, 2017)
khwan ash-Shafa is a bevy of peripatetic secret in the field of science field. As according to its the name Ikhwan ash-Shafa means